Numerical Investigation of High-Temperature Thermal Energy Storage Systems Using Concrete and Nitrate Salts: Optimization and Performance Analysis - Ayenew, Tewodros Eskemech; Asefa, Natnale Sitotaw (International Journal of Advanced Science Computing and Engineering, 2025)
This study conducts a numerical analysis of high-temperature Thermal Energy Storage (TES) systems, focusing on concrete used as a sensible heat storage material and potassium nitrate (KNO₃) as a phase change material (PCM). The study aimed to enhance the performance of TES systems in Concentrated Solar Power (CSP) plants by optimizing the number of Heat Transfer Fluid (HTF) tubes and analyzing different storage bed configurations. A 3D numerical model was developed using COMSOL Multiphysics 4.3a to simulate heat transfer processes, including fluid flow, conduction, convection, and phase change. A grid independence test ensured the accuracy of the simulations. The research identified that 25 HTF tubes provide an optimal balance between heat transfer efficiency and material usage in the nitrate salt TES model. Additionally, the cylindrical storage bed configuration reduced charging time by over 20% compared to a rectangular configuration. The results indicate that concrete can store up to 15 MJ of thermal energy, making it a viable option for CSP applications. The study also highlights the potential of embedding highly conductive materials like copper to enhance heat transfer. Recommendations for future work include exploring TES system performance under turbulent flow conditions and for intermediate temperature applications.